Monetary integration ahead of trade integration in East Asia? - Kwanho Shin; Yunjong Wang (Osaka University, Institute of Social and Economic Research (ISER), 2003)
Regionalism is taking two forms. It is occurring firstly through free trade arrangements and secondly through monetary arrangements. In this paper, we highlight the issues related to the reversal of sequence between trade integration (free trade agreement) and monetary integration (a monetary union). While the Euro area pursued trade integration first, from a theoretical point of view, there is no clear reason for introducing trade integration ahead of monetary integration. On the contrary we point out many good reasons for forming a monetary union before a free trade agreement.
Keywords: E32; F36; F41; 330; monetary union; monetary integration; free trade agreement; Währungsunion; Freihandelszone; Wirtschaftsintegration; Ostasien